The Dutch aid and trade policy: Policy discourses versus development practices in the Kenyan water and sanitation sector. (September 2019) - Savelli, Elisa; Schwartz, Klaas; Ahlers, Rhodante
Recent aid and trade policies reveal a 'paradigm shift' in which traditional donors have moved away from a focus on poverty alleviation and returned to an approach firmly aimed at economic growth. In prioritising economic growth in their development agenda, donors encourage the private sector as an active partner in development. Dutch development aid is exemplary in following this international trend. By examining development projects financed by Dutch development aid in the Kenyan water supply and sanitation sector, this article analyses to what extent these projects achieve the policy objectives of increasing private sector involvement and investment in development projects. This analysis reveals that both private sector involvement and investment do not materialise in practice. Instead the policy impacts the landscape of non-profit development organisations by pushing them to adopt and incorporate behaviour and practices usually associated with the private sector or to pursue projects targeting the private sector. Rather than leading to increased private sector involvement, the policy thus stimulates a hybridisation of development organisations in which the boundaries between non-profit organisations and private sector companies become increasingly blurred. This process of hybridisation is supported by the Dutch Government as it needs these hybrid organisations to claim success of its aid and trade policy. What results is a rather paradoxical situation where hybrid non-profit organisations are needed to claim success for a policy fostering private sector involvement.